1990
DOI: 10.1007/bf02394716
|View full text |Cite
|
Sign up to set email alerts
|

Assemblage stability in stream fishes: A review

Abstract: ABSTRACT/We quantified the stability of nine stream fish assemblages by calculating coefficients of variation of population size for assemblage members. Coefficients of variation were high and averaged over 96%; indicating that most assemblages were quite variable. Coefficient of variation (CV) estimates were not significantly affected by: (1) years of study, (2) mean abundance, (3) familial classification, or (4) mean interval between collections. We also detected minor regional differences in CVs. The high v… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

13
158
0
11

Year Published

1995
1995
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 172 publications
(182 citation statements)
references
References 37 publications
(25 reference statements)
13
158
0
11
Order By: Relevance
“…Under natural conditions, patterns and processes observed in fish assemblages are strongly influenced by multiple factors operating over a range of spatial and temporal scales (Horwitz, 1978;Schlosser, 1987;Tonn, 1990;Oberdoff et al, 1995;Ostrand & Wilde, 2002;Hoeinghaus et al, 2007). On a local scale, physical and chemical factors appear to determine species richness in variable environments (Gorman & Karr, 1978;Rahel, 1986;Schlosser, 1991;Matthews, 1998;Bond & Lake, 2003;Gerhard et al, 2004), while biological ones are more important in stable environmental conditions (Ross et al, 1985;Grossman et al, 1990). On larger spatial scales, physical factors such as spatial position within the drainage network (Osborne & Wiley, 1992;Grenouillet et al, 2004;Smith & Kraft, 2005), river size (Livingstone et al, 1982;Hugueny, 1989), climate (Hughes & Gammon, 1987), along with historical factors (e.g., speciation and dispersal) (Oberdoff et al, 1995), co-determine the composition of available species from which local communities are assembled.…”
Section: Introductionmentioning
confidence: 99%
“…Under natural conditions, patterns and processes observed in fish assemblages are strongly influenced by multiple factors operating over a range of spatial and temporal scales (Horwitz, 1978;Schlosser, 1987;Tonn, 1990;Oberdoff et al, 1995;Ostrand & Wilde, 2002;Hoeinghaus et al, 2007). On a local scale, physical and chemical factors appear to determine species richness in variable environments (Gorman & Karr, 1978;Rahel, 1986;Schlosser, 1991;Matthews, 1998;Bond & Lake, 2003;Gerhard et al, 2004), while biological ones are more important in stable environmental conditions (Ross et al, 1985;Grossman et al, 1990). On larger spatial scales, physical factors such as spatial position within the drainage network (Osborne & Wiley, 1992;Grenouillet et al, 2004;Smith & Kraft, 2005), river size (Livingstone et al, 1982;Hugueny, 1989), climate (Hughes & Gammon, 1987), along with historical factors (e.g., speciation and dispersal) (Oberdoff et al, 1995), co-determine the composition of available species from which local communities are assembled.…”
Section: Introductionmentioning
confidence: 99%
“…In contrast, unpredictable flash floods that frequently occur in temperate streams cause strong disturbances to aquatic communities (Junk et al, 1989;Poff & Allan, 1995), and the process of recovery after disturbance is very dynamic and complex (Grossman et al, 1990). Predictable and lasting aquatic and terrestrial phases permit more efficient use of resources (Junk et al, 1997b).…”
Section: Introductionmentioning
confidence: 99%
“…For instance, after analysing data from a survey of a stream fish community over a 16 years period, GROSSMAN et al (1982) concluded to the existence of stochastic stream fish assemblages in which species abundance rankings do not remain constant from year to year despite temporally stable habitat structure. This conclusion has been challenged on many grounds (see références in GROSSMAN et al [1990]) and most of the axes listed above have been involved in the debate.…”
Section: Discussionmentioning
confidence: 99%
“…(2) Selon la classification proposée par GROSSMAN et al (1990) basée sur le CV moyen de l'abondance des espèces, tous les peuplements étudiés rentrent dans la catégorie des peuplements à fortes fluctuations interannuelles. Cependant certaines populations (les salmonidés en Bretagne par exemple) présentent une faible variabilité de leur densité.…”
Section: Résuméunclassified
See 1 more Smart Citation